Effects of Aerobic Exercise on Quality of Life in Residents of Geriatric Homes, Ahvaz, Iran - Samira Borzoo; Aliasghar Arastoo; Roya Ghasemzade; Shahla Zahednezhad; Abdolhamid Habibi; Seyed Mahmood Latifi (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: Some studies show that quality of life in elderly can change due to aging process and its natural limitations. There are many methods to improve quality of life in old age, and doing simple physical exercises are among the easiest and the most cost effective methods that can improve quality of life in old persons. This study investigates the effect of aerobic exercise on quality of life in 60-75 years old residents of geriatric homes, Ahvaz, Iran 1389. Methods & Materials: In this study SF36 questionnaire was administrated to a randomly selected sample of 50 residents of geriatric homes in Ahvaz, Iran, 1389. These sample were randomly allocated to two groups: the experimental group (n=25) and control group (n=25). The members of experimental group received exercise for 8 weeks (three sessions per week). Quality of life measured in both groups before and after intervention. Data was analyzed by use of independent sample t- test and paired t-test. Results: Results did not show a significant difference between two groups in mean of the quality of life levels before intervention (P>0.05), however, this difference changed significantly inconsequent to intervention (P<0.05). Conclusion: According to the result of the study, exercise program was effective to promote elderly quality of life levels, therefore it can be used as simple and complementary method for improving elderly quality of life.